Dapatkah Altruism Mendorong Konsumen Untuk Melakukan e-WOM? - Alan Rusdiana; L Suparto; Deni Istiono (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Before the internet appeared, consumers usually talked about various kinds of productsand services directly or face to face. This can be considered as word of mouth (WOM)communication. However, along with the internet, there has been a shift related to wordof mouth (WOM) to electronic word of mouth (e-WOM). e-WOM is carried out based onexperiences related to feelings after using a product or service. Usually consumerfeelings will lead to a sense of satisfaction or not after using a product or service. Incarrying out e-WOM activities, everyone must have different goals which are inaccordance with the motivation of each individual. One thing that is consideredimportant when doing e-WOM is altruism motivation.This study aims to determine the effect of altruism on consumer behavior to share eWOM. This type of research is classified as associative research. The population in thisstudy are all students of the Faculty of Economics and Business, Majalengka Universitywho use Tokopedia e-commerce. The sample in this study amounted to 100 people whowere taken using accidental sampling technique. The data analysis method usedmultiple linear regression analysis which first tested the research instrument and theclassical assumption test, then tested the hypothesis of the SPSS 21 program.Based on the hypothesis test, it was found that altruism motivation has a positive andsignificant effect on e-WOM behavior. That is, the higher the altruism possessed byconsumers, the higher the willingness of consumers to carry out e-WOM on Tokopediae-commerce.